Research on teaching mode driven by smart education concept - Liu, Li; Xu, Chonghao (Universitas Ahmad Dahlan, 2023)
Background: The rapid development of science and technology, the Internet, big data, artificial intelligence and other technologies have had a huge impact on all walks of life in the society.With the continuous deepening of modern information technology such as artificial intelligence, big data, and the Internet of Things in education and teaching. Contribution: Smart education can promote the transformation of education concepts, reshape the space and structure of education and learning, promote fundamental changes in the level and structure of the education system, and lead the education system to overall innovation. Method: Propose a Smart education realizations teaching model that can bring prerequisites for the upgrading of digital education. Results: Smart education is a high level form of education modeling and an essential requirement for education information to enter a new stage. Conclusion: The proposed model can effectively address the shortcomings of traditional teaching methods and has effectiveness.